The effect of study-abroad experience on lexical translation among interpreting students - Wang, Ruiyuan; Han, Jing; Di Biase, Bruno; Antoniou, Mark (Frontiers in Psychology, 2023)
This study investigates the impact of study-abroad experience (SAE) on lexical translation among 50 Chinese (L1)-English (L2) interpreting students. Participants were divided into 2 groups based on their experience abroad. Both groups consisted of 25 unbalanced L2 learners who were matched in age, working memory, length of interpreting training, and L2 proficiency. Bidirectional word translation recognition tasks, from L1 to L2 and L2 to L1, highlighted several key findings: (1) both groups were significantly more accurate and faster from L2 to L1 than in the reverse direction; (2) the Study Abroad (SA) group was more inclined to respond quickly at the risk of making errors, whereas the non-study abroad (NSA) group tended to be more cautious, prioritising accuracy over speed; (3) the SA group were more balanced and consistent in their performance across lexical translations in both directions than the NSA group. These results emphasise the potent effect of SAE in resolving bilinguals' language competition, especially in streamlining language switching, a cognitive process critical for interpreting students engaging daily with dual languages.This is a provisional file, not the final typeset article their lexical processing, with a faster and more accurate performance from their L2 to their L1 than in the reverse direction, indicating an advantage in this direction (